Reciprocal Influence of Depressive Symptoms Between Mothers and Fathers During the First Postpartum Year: A Comparison Among Full-Term, Very Low, and Extremely Low Birth Weight Infants - Neri, Erica; Giovagnoli, Sara; Genova, Federica; Benassi, Mariagrazia; Stella, Marcello; Agostini, Francesca (Frontiers in Psychiatry, 2020)
Background: Perinatal depression (PND) in mothers and fathers of very low and extremely low birth weight (VLBW and ELBW) infants has not been studied extensively. In particular, no studies investigated the reciprocal influence of depressive symptoms during the first 12 months postpartum. This study aimed at exploring the impact of the severity of prematurity on maternal and paternal PND during the first postpartum year; specifically, we used an Actor–Partner Interdependence Model (APIM) to test the interdependence of both partners on depressive symptoms. Methods: 177 mothers and 177 fathers were recruited, divided in 38 couples with ELBW infants, 56 with VLBW and 83 of Full-Term (FT) infants. PND was evaluated by the Edinburgh Postnatal Depression Scale (EPDS) at 3, 9 and 12 months postpartum (corrected age for preterm infants). Results: Maternal depressive symptoms at 3 months were positively related to those at 9 and 12 months, in the 3 groups. Conversely, paternal depressive symptoms assessed at 3 months were positively related to those measured at: 9 months for ELBW group, 12 months for VLBW group, 9 and at 12 months for FT condition. Furthermore, a significantly positive partner effect was observed, regarding the influence of 3 month-maternal depressive symptoms on paternal depressive symptoms at 9 months, but only in the case of VLBW group. Conclusion: Prematurity represents a very specific scenario in the transition to parenthood, leading to specific reactions in mothers and fathers, especially in high-risk condition. Results should be deepened given the relevance of their clinical implications.